2021
DOI: 10.21203/rs.3.rs-215251/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Relationship Between the Atherogenic Index of Plasma and Arterial Stiffness in Essential Hypertensive Patients from China: A Cross-Sectional Study

Abstract: Background: The atherogenic index of plasma (AIP) always remains in a potential association with the arterial stiffness, however, in large hypertensive patient populations, this relation is not fully discovered and needs to be studied in depth. The present analysis thus sought to further explore the association that exists between AIP and arterial stiffness in patients diagnosed with arterial hypertension in China.Methods: This cross-sectional study analyzed 4744 Chinese individuals with essential hypertension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
(56 reference statements)
0
4
0
Order By: Relevance
“…Zhou et al, Wang et al, and Shanker et al reported that AIP was an independent and powerful predictor of the presence of CAD. 8,[20][21][22] Furthermore, evidence suggests AIP may serve as an independent predictor for arterial stiffness, coronary artery calcification progression, rapid coronary plaque progression, instent restenosis, and total coronary occlusion. [22][23][24][25][26] These studies are generally related to the relationship of the AIP index with coronary artery disease's anatomical features and severity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhou et al, Wang et al, and Shanker et al reported that AIP was an independent and powerful predictor of the presence of CAD. 8,[20][21][22] Furthermore, evidence suggests AIP may serve as an independent predictor for arterial stiffness, coronary artery calcification progression, rapid coronary plaque progression, instent restenosis, and total coronary occlusion. [22][23][24][25][26] These studies are generally related to the relationship of the AIP index with coronary artery disease's anatomical features and severity.…”
Section: Discussionmentioning
confidence: 99%
“…8,[20][21][22] Furthermore, evidence suggests AIP may serve as an independent predictor for arterial stiffness, coronary artery calcification progression, rapid coronary plaque progression, instent restenosis, and total coronary occlusion. [22][23][24][25][26] These studies are generally related to the relationship of the AIP index with coronary artery disease's anatomical features and severity. However, there was no further study on the relationship between AIP and the functional severity of coronary artery stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…As was independently and strongly associated with the risk of CAD in special populations such as very young adults and postmenopausal women, who usually had the unique risk factor profile 25,26) . Furthermore, mounting evidence suggests AIP may serve as an independent predictor for arterial stiffness, coronary artery calcification progression, and the rapid progression of coronary plaque, all of which were powerful predictors of adverse cardiac events 15,27,28) . Most importantly, Qin et al and Ma et al demonstrated that increased AIP upon admission correlated positively with the worse long-term prognosis in patients after PCI.…”
Section: Association Of Aip With the Risk Of Des-isr In Different Subgroupsmentioning
confidence: 99%
“…In our study, subjects were divided into three categories according to BMI levels (< 25 kg/m^2, control group; 25-30 kg/m^2, overweight; and ≥ 30 kg/m^2, general obesity) [25][26][27]30]. Central obesity was defined as WHR ≥ 0.9 for males and ≥ 0.85 for females [39].…”
Section: Clinical Data Collectionmentioning
confidence: 99%